Evaluation of the Energy Performance of Adobe Structures Constructed Using Modern Techniques for a Sustainable Future: The Case of Elazığ - Demirtaş, Muhammed Emin; Gulten, Ayca (My University, 2025)
Natural materials offer significant advantages in terms of energy efficiency in buildings. Materials such as earth, adobe, and stone stand out due to their high thermal mass, which enables them to provide cooling during the summer and retain heat during the winter. Among these natural materials, earth-derived materials are also notable for their low energy costs. This research evaluates the energy performance of a building constructed using the rammed earth technique in the Keban district of Elazığ. As a case study, the \"Women's Education and Production Center Project,\" designed and implemented by Architect Özgül Öztürk in the Keban district of Elazığ, is examined. Comparisons are made with the energy performance that would result if the same building were constructed using concrete and sandwich panel materials. This study aims to analyze the energy performance of rammed earth, concrete, and sandwich panel materials and to determine the environmental impacts of these materials. In this context, the study focuses on alternative materials that could contribute to future sustainable construction. In this research, energy performance analysis was conducted using Revit. This program examined the thermal insulation capacities and energy consumption rates of buildings constructed with different materials. The results of the study indicate that rammed earth material is superior in energy efficiency. These evaluations also highlight the contributions of natural and breathable materials, such as rammed earth, to the environmental sustainability of buildings. It is considered that such materials could emerge as a sustainable alternative in future construction.
Keywords: Adobe; Earth; Energy Performance; Breathable Material; Natural Material; Rammed Earth; Sustainable Material